INDUSTRIAL ENTERPRISE RISK MANAGEMENT MECHANISMS AGGREGATION AND INTEGRATED VISUALIZATION OF RISK ASSESSMENT RESULTS - Zaripov , Rushan; Murakaev, Ilnur; Ryapukhin, Anatoly (Revista Inclusiones, 2020)
In the framework of this article, industrial enterprise unification issues of the departments’ functional related to control and audit activities implementation, internal audit, risk management, and controlling are considered. It is proposed to combine these directions into a single cluster, forming a dynamic matrix of functionality, individual cells of which are activated and complement each other depending on the tasks. An algorithm for identifying the organization’s main risk factors based on the international standard ISO 31000:2018 is presented. Recommendations are given on risks histogram formation that allows monitoring the organization’s problem areas in a single scale of indicators.